Pengalaman Kerja Sebagai Pemediasi Pengaruh Kerjasama Tim Terhadap Efektivitas Kerja Karyawan - Junita, Audia; Pentana, Sopi; Sitorus, Indra Syahputra (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2022)
This study aims to determine whether the work experience in mediating the influence of teamwork on the work effectiveness of the employees of PT. Bank SUMUT Medan. The population in the study were employees of the marketing division (Funding Officer and Account Officer) at PT Bank Sumut Medan totaling 196 people and a sample of 132 respondents who were determined by proportional random sampling technique from 3 branch offices namely Medan Main Branch Office, Medan Iskandar Muda Branch Office, and Medan Sukaramai Branch Office. The analysis technique used is Mediated Regression Analysis (MRA). The results showed that work experience mediates the effect of teamwork on the work effectiveness of employees at PT. Bank SUMUT Medan. The suggestions are to improve teamwork at PT. Bank SUMUT Medan, the leadership needs to make intense and effective communication and cooperation beetween employees in order to contribute the progress of the company. There are needs to facilitate joint activities in the company either through games, recreation, problem solving, and others that can build good relationships, grow a sense of belonging, mutual support, and mutual trust in a work team.